The influence of silver nanoparticles on the stimulated luminescence of rhodamine 6G solutions - Ibrayev, N.Kh.; Zeinidenov, A.K.; Aimukhanov, A.K. (Pleiades Publishing, 2014)
The influence of silver nanoparticles on the spontaneous and stimulated luminescence of rhodamine 6G molecules in aqueous solutions is studied. It is found that the laser photoexcitation of the dye solution gives rise to spontaneous fluorescence, which, with increasing pump power, transforms into stimulated laser radiation and superluminescence. Addition of silver nanoparticles to rhodamine 6G solutions enhances all types of luminescence and lowers the generation threshold for both types of the stimulated emission. The dependences of the laser radiation and superluminescence intensities on the concentration of silver nanoparticles correlate with the data on the spontaneous fluorescence.